PTH-002 Ercp: Balancing Demand, Training And Manpower In South East Region. (9th June 2014) - Jeevagan, A; Rai, P; Bird, G
Abstract : Introduction: The purpose of this survey is to assess trainees attitudes and exposure to ERCP training in the south east region of England and also to explore the demand for ERCP endoscopists in future. Methods: Two separate short survey questionnaires were sent using an online survey tool between July 2012 to October 2012. One was sent to the trainees and the second questionnaire was sent to the Consultant Gastroenterologists in this region. In some instances survey was conducted through telephone, e-mail or in person. Results: Out of 43 trainees, nearly 10/43(23%) were getting trained in ERCP, 14/43 (33%) mentioned that their training needs had been assessed, 32/43 (75%) were not aware of the current need for consultant ERCPs in this region. Among the trainees who do not want to get trained in ERCP, 5/33 (16%) of them had interest in other sub-specialty, 4/33(14%) considered it a difficult procedure to get trained and 3/33(9%) did not have any appropriate guidance. The other reasons include high risks and complication 3/33 (9%), longer duration of training 1/33(3%) and lack of training facilities 2/33 (6%). Among the trainees who performed ERCPs only 2/10(20%) had done more than 100 procedures. None of them got more than 75% selective duct cannulation rate. Majority of trainees, about 30/43 (70%) of them pointed out that ERCP should not be an essential skill for gaining a consultant job. Out of 55 consultants gastroenterologists 27/55 (50%) of them perform ERCP. Of these 27 consultants, 18/27 (67%) trained at least one trainee. Only 3/27 (11%) consultants mentioned that they would stop doing ERCP procedures in the next 5 years and 6/27(22%) within next 10 years. 7/27 (25%) of the consultants thought that their colleague/colleagues would take over the ERCP service when they retire and 12/27 (45%) thought that new ERCP consultants will be recruited. Conclusion: This survey suggests that there is currently only a need for 2–3 trainees to be learning ERCP if the current demand is stable. The number of trainees training in ERCP need to be very small unless we accept that the trained ERCP endoscopists might give up on transition to consultant. There is a disparity in that consultants claim they are delivering ERCP training but this is not reflected in the results of the trainee's responses. Most of the trainees are in their early stage of in the ERCP training. None of the trainees got over 75% selective cannulation rate. Disclosure of Interest: None Declared.